Improving complementary feeding practices, programs and policies for optimal early childhood nutrition in Kenya: What would work? - Patrick Codjia; Laura Kiige; Christiane Rudert; Stella Nordhagen; Ty Beal; Veronica Kirogo; Flaminia Ortenzi; Wendy Gonzalez; Penjani Kamudoni; Aashima Garg (Wiley, 2024)
Abstract Complementary feeding practices are greatly influenced by local contexts. Therefore, national home‐grown evidence, policies and guidelines are critical to improving infant and young children's diets. This Special Issue has provided a comprehensive, evidence‐based analysis of the situation, gaps and context‐specific opportunities for improving young children's diets in Kenya. The primary research findings of the Special Issue supported the identification of a set of recommendations articulated across the four systems (food, health, water, sanitation and hygiene [WASH] and social protection) to improve food availability and accessibility in Kenya at the national and subnational levels. It is anticipated that the decentralised government functions seen in Kenya provide a strong opportunity to develop and mainstream context‐specific recommendations into action. This Special Issue recommends adopting a multi‐sectoral systems approach, including a shared vision, joint planning, implementation and monitoring, towards improving young children's diets with a focus on service delivery as well as scaled‐up community social behaviour change interventions. In particular, the approach should entail advocacy for policy revisions for service delivery that support complementary feeding and development of costed implementation strategies in support of the same, across four critical systems-food, health, WASH and social protection, along with, the strengthening of national coordination, monitoring and accountability structures as per the Kenya Nutrition Action Plan. Finally, the development of a legal framework for enhanced accountability from all relevant sectors towards sustainable, nutritious, safe and affordable children's diets. These recommendations provide a clear direction in addressing the complementary feeding challenges, which the primary research of this Special Issue has presented.